Cooperation Between Cancer and Fibroblasts in Vascular Mimicry and N2-Type Neutrophil Recruitment via Notch2–Jagged1 Interaction in Lung Cancer - Tsai, Ying-Ming; Wu, Kuan-Li; Liu, Yu-Wei; Chang, Wei-An; Huang, Yung-Chi; Chang, Chao-Yuan; Tsai, Pei-Hsun; Liao, Szi-Hui; Hung, Jen-Yu; Hsu, Ya-Ling (Frontiers in Oncology, 2021)
Abstract: A requirement for tumor development and metastasis is through angiogenesis, which involves the cooperation in a tumor microenvironment. Vascular mimicry (VM) is a process in which cancer cells, rather than endothelia, create an alternative perfusion system. This study provides evidence that cancer-associated fibroblasts (CAFs) support VM formation in lung cancer. Although H1299 and CL1-0 lung cancer cells were unable to form capillary-like structures, VM formation was induced by CAFs in both in vitro and in vivo experiments. Notch2–Jagged1 cell–cell contact between cancer cells and CAFs contributes to the formation of VM networks, supported by Notch intracellular domain (NICD) 2 nuclear translocation and N2ICD target gene upregulated in lung cancer cells mixed with CAFs. The polarization of tumor-promoting N2-type neutrophil was increased by VM networks consisting of CAF and cancer cells. The intravasation of cancer cells and N2-type neutrophils was increased because of the loose junctions of VM. Disruption of cancer cell–CAF connections by γ-secretase inhibitors enforced the anticancer effect of anti-vascular endothelial growth factor antibodies in a mouse model. This study provides the first evidence that CAFs induce lung cancer to create vascular-like networks. These findings suggest a therapeutic opportunity for improving antiangiogenesis therapy in lung cancer.